DEVELOPMENT OF WHITE OYSTER MUSHROOM CULTIVATION BUSINESS IN ORDER TO INCREASE PEOPLE'S INCOME BONGKORAN HAMLET, SRAGI VILLAGE, SONGGON DISTRICT BANYUWANGI DISTRICT - Ainur Rofiq; Syamsul Arifin (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
The cultivation of white oyster mushrooms is able to bring very tempting profits both on a small and large scale. This is inseparable from the high demand and selling value of white oyster mushrooms. This research method uses field research, which is research carried out on an event that actually happened. The approach used is the phenemonological approach. Sumber data in this study, primary data and secondary data. The techniques used to obtain data in the field are in accordance with technical data, namely Observation, Interviews, and Documentation. Meanwhile, the data analysis technique goes through three stages, namely data reduction, data presentation, and verification. Research results; 1). The cultivation conditions of white oyster mushrooms in Bongkoran Hamlet can still be developed properly but are limited by the place or location of development. 2). marketing strategy, the harvest of white oyster mushroom farmers is sold to Business Partners. 3). Factors affecting the development of white oyster mushroom productivity: First, technical factors, Second, economic factors, Third, social factors, Fourth, the availability of raw materials and production land, Fifth, Human resources of white oyster mushroom farmers are still considered minimal, Sixth , the use of technology is still tersaid gabtek